LRP1 protects against excessive superior mesenteric artery remodeling by modulating angiotensin II–mediated signaling - Jackie M. Zhang; Dianaly T. Au; Hisashi Sawada; Michael K. Franklin; Jessica J. Moorleghen; Deborah A. Howatt; Pengjun Wang; Brittany O. Aicher; Brian Hampton; Mary Migliorini; Fenge Ni; Adam E. Mullick; et al. (JCI Insight, 2023)
Vascular smooth muscle cells (vSMCs) exert a critical role in sensing and maintaining vascular integrity. These cells abundantly express the low-density lipoprotein receptor–related protein 1 (LRP1), a large endocytic signaling receptor that recognizes numerous ligands, including apolipoprotein E–rich lipoproteins, proteases, and protease-inhibitor complexes. We observed the spontaneous formation of aneurysms in the superior mesenteric artery (SMA) of both male and female mice in which LRP1 was genetically deleted in vSMCs (smLRP1–/– mice). Quantitative proteomics revealed elevated abundance of several proteins in smLRP1–/– mice that are known to be induced by angiotensin II–mediated (AngII-mediated) signaling, suggesting that this pathway was dysregulated. Administration of losartan, an AngII type I receptor antagonist, or an angiotensinogen antisense oligonucleotide to reduce plasma angiotensinogen concentrations restored the normal SMA phenotype in smLRP1–/– mice and prevented aneurysm formation. Additionally, using a vascular injury model, we noted excessive vascular remodeling and neointima formation in smLRP1–/– mice that was restored by losartan administration. Together, these findings reveal that LRP1 regulates vascular integrity and remodeling of the SMA by attenuating excessive AngII-mediated signaling.